Optimized Soil-Footing Interaction Analysis for Edge Footings Subjected to Eccentric Loading - Saraogi, Anurag; Garg, Vivek; Dubey, S.K. (International Journal of Aquatic Research and Environmental Studies, 2026)
Footings subjected to eccentric loading often experience significant challenges such as uneven pressure distribution, excessive tilt, and differential settlement—particularly for columns located at the edge or corner of a structure. This study proposes a novel, performance-based optimization approach using modified geometries of footings to address these issues effectively and economically. Three innovative configurations are introduced: Isolated Footing with Insertion (IFI), Tapered Footing with Insertion (TFI), and Trapezoidal Tapered Footing with Insertion (TTFI). These designs aim to enhance stability, reduce tilt, and ensure uniform pressure distribution while maintaining or reducing the overall volume of concrete required. Using finite element modeling on ANSYS for Soil-Footing interaction (SFI) analysis, the performance of each configuration is evaluated and compared against conventional isolated footings. The results reveal that the TTFI configuration offers superior performance, achieving near-uniform pressure distribution and significantly reduced tilt without increasing volume and geometrical modifications involving insertions and tapering can provide a safe, efficient, and economical solution to the longstanding problem of footing instability under eccentric loads